Peculiarities of Using the Charging Coils in Fast LTD Cavities; 20th International Symposium on High-Current Electronics (ISHCE) - Aleksenko V. O. Vladislav Olegovich; Kondratiev S. Sergey; Sinebryukhov V. Vadim; Volkov S. Sergey; Kim A. Alexander (2018, 2018)
Title screen